WATER LEVEL FLUCTUATION AND HABITAT USE PATTERN OF WINTERING WATERBIRDS IN THE JUNAM RESERVOIR AREA, SOUTH KOREA - Lee Chan-Woo; Gu-Yeon Kim; Ji-Deok Jang; Bishnu B Bhandari; Gea-Jae Joo (Tropical Life Sciences Research, 2006)
Water level fluctuation and changes of wintering waterbird community at the Junam Reservoir areas (Junam Reservoir, Dongpan Reservoir, Samnam Reservoir) were investigated from October 2002 to March 2005. To analyse the relationship between water level fluctuation and habitat use pattern of waterbirds, the annual water level was measured at Dongpan Reservoir; and wintering waterbirds in the area were annually monitored. Most waterfowls (ca. 6000 individuals) utilized the Junam Reservoir for feeding and resting ground in the early winter (October to middle December). However, waterbirds moved to the Dongpan Reservoir since December, after the decrease of water level. During winter 2002/2003, a number of dabbling ducks (r2 = 0.97), swans and geese (r2 = 0.99), and shorebirds (r2 = 0.95) had significant relationship with the decrease of water depth; while relationship with diving waterbirds (r2 = 0.63) was relatively low. In 2003/2004 only swans and geese (r2 = 0.90) were highly influenced by the water level, however other groups were not affected by water level changes because of relatively low fluctuation. In 2004/2005, diving waterbirds (r2 = 0.62) and shorebirds (r2 = 0.62) showed weak relationship with water depth. Relatively, the seasonal 2003/2004 and 2004/2005 did not have sufficient summer rainfall and also the regulation of water level was not good for sustainable waterbird habitats. To maintain the Dongpan Reservoir as a waterbirds wintering ground, not only systematic regulation of water level, in wintering season, but also the regulation of summer water level, is very important for food plant growth and animal food sources such as benthos and fish.